WWOX-rs13338697 genotype predicts therapeutic efficacy of ADI-PEG 20 for patients with advanced hepatocellular carcinoma - Chu, Yu-De; Liu, Hui-Fen; Chen, Yi-Chen; Chou, Chun-Hung; Yeh, Chau-Ting (Frontiers in Oncology, 2022)
Previous studies have identified three single nucleotide polymorphisms (SNPs): GALNT14-rs9679162, WWOX-rs13338697 and rs6025211. Their genotypes are associated with therapeutic outcomes in hepatocellular carcinoma (HCC). Herein, we examined whether these SNP genotypes could predict the clinical outcome of HCC patients treated with ADI-PEG 20. Totally 160 patients with advanced HCC, who had previously been enrolled in clinical trials, including 113 receiving ADI-PEG 20 monotherapy (cohort-1) and 47 receiving FOLFOX/ADI-PEG 20 combination treatment (cohort-2), were included retrospectively. The WWOX-rs13338697-GG genotype was associated with favorable overall survival in cohort-1 patients (P = 0.025), whereas the rs6025211-TT genotype was associated with unfavorable time-to-tumor progression in cohort-1 (P = 0.021) and cohort-1 plus 2 patients (P = 0.008). As ADI-PEG 20 can reduce plasma arginine levels, we examined its pretreatment levels in relation to the WWOX-rs13338697 genotypes. Pretreatment plasma arginine levels were found to be significantly higher in patients carrying the WWOX-rs13338697-GG genotype (P = 0.006). We next examined the association of the WWOX-rs13338697 genotypes with WWOX tissue protein levels in 214 paired (cancerous/noncancerous) surgically resected HCC tissues (cohort-3). The WWOX-rs13338697-GG genotype was associated with decreased tissue levels of WWOX and ASS1. Mechanistic studies showed that WWOX and ASS1 levels were downregulated in hypoxic HCC cells. Silencing WWOX to mimic low WWOX protein expression in HCC in patients with the WWOX-rs13338697-GG genotype, enhanced HIF1A increment under hypoxia, further decreased ASS1, and increased cell susceptibility to ADI-PEG 20. In summary, the WWOX-rs13338697 and rs6025211 genotypes predicted treatment outcomes in ADI-PEG 20-treated advanced HCC patients. The WWOX-rs13338697-GG genotype was associated with lower tissue WWOX and ASS1 levels and higher pretreatment plasma arginine levels, resembling an arginine auxotrophic phenotype requires excessive extracellular arginine supply. Silencing WWOX to mimic HCC with the WWOX-rs13338697-GG genotype further stimulated HCC cell response to hypoxia through increased HIF1A expression, leading to further reduction of ASS1 and thus increased cell susceptibility to ADI-PEG 20.